Sighting patterns reveal unobserved pupping events to revise reproductive rate estimates for Hawaiian monk seals in the main Hawaiian Islands. Issue 2 (23rd November 2020) - Robinson, Stacie J.; Harting, Albert L.; Mercer, Tracy; Johanos, Thea C.; Baker, Jason D.; Littnan, Charles L.
Abstract: We used sighting reports, including decades of citizen‐reported Hawaiian monk seal ( Neomonachus schauinslandi ) sightings, to describe female breeding biology and reproductive success in the main Hawaiian Islands. We first used this data set to describe the timing of events in the female reproductive cycle. We then conducted an expert review of patterns in sighting histories to detect unobserved pupping events. Finally, we estimated the age‐specific reproductive curve for female monk seals in the main Hawaiian Islands. Charting reproductive cycles showed indications of the robust condition of female monk seals in the main Hawaiian Islands; they nursed pups 12% longer than their counterparts in the Northwestern Hawaiian Islands and regained condition to molt more quickly after weaning a pup. By examining sighting histories, we were able to infer 25 unobserved pupping events that had previously gone uncounted. We accounted for additional uncertainty with a randomization procedure. After accounting for unobserved pupping events, the age‐specific reproductive rate of main Hawaiian Islands monk seals exceeded 0.70 for prime aged females (8–18 years). This is the highest reproductive rate reported for any of the Hawaiian monk seal breeding sites, illustrating the important role of the main Hawaiian Islands population in Hawaiian monk seal recovery.